Development of learning media for minangkabau natural culture in elementary schools - Zuwirna, Zuwirna; Amilia, Winanda (COUNS-EDU: The International Journal of Counseling and Education, 2022)
This research develops learning media products in the form of Minang language story books for learning Minangkabau Natural Culture. This subject is one of the local content subjects at the Padang City Elementary School, West Sumatra Province. The development of this learning media is motivated by the learning needs of Minangkabau Natural Culture which does not yet have an alternative media in the learning process. This study uses a development research approach using the ADDIE model which consists of the Analyze, Design, Development, Implementation, Evaluation stages. This research is very important to do because it sees the lack of learning media developed for Minangkabau Natural Culture subjects for elementary school students. The results showed that the developed learning media had a good usability level with an average score of 89.1%. Testing the effectiveness of the learning media also showed a score of 85.6% in the very good category. Thus, from the results of the development carried out, it can be concluded that the use of learning media can improve students' understanding and learning outcomes of Minangkabau Natural Culture Subjects in elementary schools.